EDUKASI PENGISIAN e-SPT UNTUK PELAKU UMKM WILAYAH KANWIL DJP JAWA BARAT II - Lucia Ari Diyani; Ratna Dewi Kusumawati; Kadek Wisnu Bhuana; Layon Hocben Hutagaol (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
This community service activity (PkM) aims to provide education and training for MSMEs by providing an understanding of terms, calculations and procedures for reporting income taxation specifically through e-SPT. The partner problems to be solved in this activity is some of UMKM in Bekasi and surrounding area does not understand about filling the SPT and using e-SPT to report their tax liability. The implemented method to solved the problem is giving education through online webinar which is held by collaboration between some lecturers in Program Studi Akuntansi Universitas Bina Insani and Kanwil DJP Jawa Barat II. The activity is divided into 3 stages: planning, implementation and evaluation sessions. The data used to measure the success of webinar are processed using the Wilcoxon Test and analysis. The results show an increase in understanding and knowledge after participating in webinar activities. It means that the goal of this PkM has been achieved. The average results of the satisfaction questionnaire show that partner (participant) is satisfied with the materials, delivery method, and whole webinar.